Software Architecture Superstream Series : Microservices ; September 9, 2020 - Ford, Neal; Hightower, Kelsey; Alagarsamy, Indu; Parsons, Rebecca; Tania, Sofia; Shapira, Gwen (O'Reilly Media, Inc., 2020)
This three-part series of half-day online events, hosted by chair Neal Ford, focuses on the hottest topics in software architecture-including microservices, essential architecture principles, and event-driven architecture and domain-driven design-giving you the insights to keep pace with what's next while still accommodating legacy needs. Both seasoned software architects and those looking to break into the field will learn new skills and the latest information on the tools and technologies they need to succeed. This is part 2 of the series, Microservices, where you will meet instructors Kelsey Hightower, Indu Alagarsamy, Rebecca Parsons, Sofia Tania, and Gwen Shapira.